Dysfunctional Uterine Bleeding: Current Concept - Methil Kannan Kutty; Siva Achanna; Nik Nasri Ismail (Universiti Sains Islam Malaysia, 2022)
The spectacular strides made in the kaleidoscopic spectrum of the etiology and treatment of dysfunctional urine bleeding (DUB)make an exciting venture for all those who are interested in recent trends in gynaecology and this raison d'etre for this book. Astounding progress in the state of the art, technology and progressive discoveries such as micro RNA etc have impacted all facets of medical disciplines in unraveling molecular mechanisms of diseases including DUB. Cognizant of this scenario with the cutting edge of modern technology and its paramount importance in understanding the basic pathogenesis of DUB, have been touched on some of the breakthroughs for clearer comprehension of certain aspects that have, hitherto, remained unclear.